Estudo comparativo entre o tratamento radioterápico com elétrons e betaterapia, após cirurgia de queloides - Oliveira Júnior, Batista de [UNESP]; Lastoria, Joel Carlos [UNESP]; da Rosa Pereira, Hamilton [UNESP]; de Arruda Silveira, Luciana Vaz [UNESP]; de Oliveira, Lívia Paludetto; Stolf, Hamilton Ometto [UNESP] (My University, 2009)
Introduction: The surgery of keloids as an individual therapy with high rates of recurrence needs adjuvant therapies as complement. Recent keloids are rich in fibroblasts, which are highly radiosensitive and what explains the good results of percutaneous radiotherapy after surgery. Objective: To compare the beta-therapy results with electron-beam technique in newly operated keloids. Material and Methods: a prospective, comparative and randomized study was outlined including patients in the immediate postoperative period of surgical excision of keloids. Divided in G1 and G2 groups respectively, they received treatment with Sr90 (beta-therapy)plates or with electrons from the linear accelerator. The monitoring lasted 10 years. The results were performed using the information from patients, photograph parameters, observation and measurement of injuries, according to the criteria: Unchanged, Regular, Good and Excellent. Results: There were 26 patients, 13 in each group. In G1, 54% presented regular and unchanged improvement criteria and 46% had good or excellent criteria. In G2, the results were respectively 23% and 77%. Conclusion: The irradiation with electron-beam is better than beta-teraphy for the treatment of keloids surgery, due to the distribution in the tissue. No radio-induced tumors were observed.
Chemabrasion for the treatment of perioral wrinkles: Clinical analysis and epidermal Langerhans cells quantification
Keywords: Electrons; Keloid; Strontium